Legal Protection of the Consumer of Genetically Modified Products in Nigeria - Fayokun, Kayode Olatunbosun (2015)
The study examined the state of the Nigerian law on the protection of consumers of genetically modified products that are now appearing in the world market. It identified the legal issues relating to genetically modified organisms and products, and considered the consumer safety concerns they have generated. It also examined the adequacy of the existing product liability and consumer safety laws, and the challenges posed by inadequate legal protection regime in the face of emerging, untested "state of technology" products in the Nigerian market.